2019
DOI: 10.2147/jhl.s195751
|View full text |Cite
|
Sign up to set email alerts
|

<p>Leadership and management competencies required for Bhutanese primary health care managers in reforming the district health system</p>

Abstract: Objective This study aims to identify the required management competencies, current competency levels, and strategies for improving the management competencies of Bhutanese primary health care (PHC) managers. Methods A quantitative method with a cross-sectional survey using self-administered questionnaires. This study recruited 339 PHC managers across Bhutan. The data were analyzed using statistical software. Results This study identified thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…However, whether the level of competence required to demonstrate these competencies varies between management levels and positions is yet to be tested. The identified competencies are consistent with studies conducted on healthcare managers in different (Dorji et al, 2019), Australia (Liang et al, 2013a, b), Oman (Al Harthy et al, 2018) and Thailand (Kitreerawutiwong et al, 2015). In a resource-constrained public hospital system, focusing on developing the core competencies amongst managers may be an effective way of improving overall management and health outcomes.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, whether the level of competence required to demonstrate these competencies varies between management levels and positions is yet to be tested. The identified competencies are consistent with studies conducted on healthcare managers in different (Dorji et al, 2019), Australia (Liang et al, 2013a, b), Oman (Al Harthy et al, 2018) and Thailand (Kitreerawutiwong et al, 2015). In a resource-constrained public hospital system, focusing on developing the core competencies amongst managers may be an effective way of improving overall management and health outcomes.…”
Section: Discussionsupporting
confidence: 82%
“…The newly included competencies of professionalism are consistent with those that have been included in the Healthcare Leadership Alliance and the American College of Healthcare Executives (Stefl, 2008) and studies from Thailand (Kitreerawutiwong et al, 2015) and Bhutan (Dorji et al, 2019).…”
Section: Discussionmentioning
confidence: 68%
“…10 Therefore, professionalism requires development in education and training in healthcare services. 10,32,34,46,47 Managers can access managerial professional development through a variety of ways. There are a number of useful mechanisms to achieve it including formal education at universities in the field of management; in-service training; in-house use of mentors and study groups; and offsite intensive training, seminars and conferences.…”
Section: Dovepressmentioning
confidence: 99%
“…Components of communication include listening with understanding, demonstrating effective relationships, verbal and visual communication, and use of factual information (eg, data), among others. 42 Effective communication is an essential component of teamwork, 43 as it reduces the chances of conflicts and promotes understanding and cohesion among team members. Various studies have demonstrated that the promotion of teamwork in health care sector hinges on understanding, effective communication, information sharing and education of health care workers on their expected roles in current health care services delivery trends.…”
Section: Discussionmentioning
confidence: 99%
“…Competence is a tool used to optimize performance in an organization, and it comprises a set of knowledge, skills and ability required to perform a given task. 42 , 46 According to The National Center for Health Care Leadership (NCHL), leaders in health organizations are expected to possess certain leadership and management competences spread across three competency domains namely people, execution, and transformation. 47 People refers to the organizational atmosphere where employees are valued irrespective of backgrounds and provides a motivating environment for them to excel; execution is about transforming vision and strategy into optimal institutional performance; and transformation is visioning, energizing, and stimulating a change process that unites communities, patients, and professionals around new models of health care and wellness.…”
Section: Discussionmentioning
confidence: 99%